MUET intensive programmes - Marziah, Ramli (Pusat Bahasa Moden dan Sains Kemanusiaan, 2009)
3 Oct 2009. Language teachers of CMLHS conducted MUET Intensive Programme to assist and guide candidates of MUET for November 2009 session.